(untitled) (Gestión y Gerencia, 2021)
This work is the result of documentary research with an exploratory and descriptive scope whose objective is to interpret the disruption based on conceptual precisions provided by different authors. The categorization of elements that encourage the appearance of disruptive events in the organization, the participation of the subject as a promoter of disruption in the organization or if it is the reverse is also analyzed. The research deciphers that the concept under study is a phenomenon typical of complex, open and organic organizations determined by Edgar Morin and Gary Dessler, since they are suitable for breaking conventionalism, taking into account self-reference, self-organization, uncertainty, diversity and clutter. It is concluded that the disruption comes from subjects capable of encouraging organizational metamorphosis, also evidencing that disruptive organizations favor the transformation of subjects, thus turning them into disruptive agents as a result of a cyclical process.